Proposed Marketing Strategy For Hotel Trio Bandung - Pane, Yullianthy Azani Putri; Paramartha, Riawan B. (The Indonesian Journal of Business Administration, 2014)
Abstract.Accommodation business growth in Bandung showed a significant increase each year. It happens to follow the growth of tourist arrivals are increasing every year. The purpose of tourist visits to Bandung varies, ranging from vacation, business, education etc. The increasing growth of hospitality industry in Bandung creating intense competition among business owners. Creativity and unusual strategies are emerged in an effort to reach the markets. Hotel Trio is one of the old hotel that has been operation since 1930, located at Jalan Gardujati, Bandung. With the increasing competition, since 2009 Hotel Trio loses its walk-in guests so that sales targets are not achieved in 2013. This is due to the lack of promotional efforts undertaken by Hotel Trio and also the lack of effort to follow the trends in community of utilization the technology.To be able to help and resolve the business issue, internal analysis, brand analysis, external analysis, situation analysis and market analysis for the customer needs to be done to get at the root causes of the problems facing the Hotel Trio. The analysis shows that the root cause of the problem is a lack of promotion and innovation that led to Hotel Trio left by the walk-in guests and hotel brand awareness unnoticed.Some of marketing strategies recommendations are proposed in response these condition. The result of strategy is renewing its positioning and targeting for walk-in guest as part of the primary needs of marketing strategy. There are also solutions in marketing mix attributes to improve the satisfaction of the guests. Renovations should be done in an effort to keep follow the times and tastes of the market at the same time to create the Hotel Trio characteristics so as the guests can enjoy the new conditions of Hotel Trio.Â Keywords: Bandung, Hotel, Marketing Strategy, Brand Awareness, Promotion